정신박약자녀의 장래보장을 위한 부모의 욕구조사 - 박순국 (연세대학교 보건대학원, 1988)
[한글] 세계인구의 1-2%를 차지하고 있다고 추정되는 정신박약자는 한 가정의 문제에서 점차 사회전체적인 문제로 되고 있다. 그동안 우리나라에서 정신박약자의 문제는 사회문제화되지 않았고 정신박약자의 부모 역시 그들 자녀의 문제를 은폐시켜 왔으며 사회적인 인식도 아직은 부족하고 국가차원의 지원 역시 미흡한 실정이다. 이에 이들 정신박약자 문제해결의 접근방법으로서 가장 심각하게 문제의식을 갖고 있을 부모들의 욕구를 파악하고 이들의 욕구가 타 장애자부모들의 촉구와 어떠한 차이가 있는가를 의료, 직업, 시설수용보호 및 장래생활보장의 4가지 측면에서 비교 연구하고 대안을 제시하고자 전국 94개 특수학교 17,371명의 학생을 대상으로 14개 특수학교에서 310명을 집락 계통표집 방법으로 표본추출 하여 수집된 301개의 질문서를 다변수 회귀분석으로 복지욕구에 영향을 주는 요인을 검토하고 κ**2-test로 집단간 변수의 상관성을 검증 분 석하였다. 1. 장애특성이 부모들의 욕구에 영향을 주는 요인으로는 장애발생시기가 늦을수록, 장애자의 성이 남자일 때, 모의 연령이 높을수록 그리고 부의 교육정도가 높을수록 자녀에 대한 복지욕구가 높으며 장애유형에 따라 복지욕구가 달랐다. 2. 정신박약자는 타 장애자보다 이환율이 낮은데 비하여 의료기관 이용빈도는 같으며, 의료욕구가 통계학적으로 유의하게 높은 것은 건강과 관련하여 의료기관을 찾는다고 할 수 있다. 3. 정신박약자 부모나 타 장애자 부모가 다같이 장애자녀를 위한 특수병원이나 특별창구를 원하고 있다. 그 이유로는 일반병원이 장애자의 특성을 이해하지 못하고 의료비 및 편의시설에 대한 불만이 많았다. 4. 정신박약자 부모는 자녀들의 취업전망이나 취업의 당연성에 대해서는 타 장애자 부모보다 회의적인데 반해 직업훈련에 대해서는 더 많은 욕구를 갖고 있었다. 따라서 정신박약자녀도 보호받으며 능력에 따라 보수를 받는 형태의 취업을 원하는 욕구가 강한 것으 로 해석할 수 있다. 5. 정신박약자 부모들이 타 장애자 부모보다 시설수용보호욕구가 통계학적으로 유의하게 높은 것은 사회적 관계의 어려움과 혼자서는 생활할 수 없다는 이유가 영향을 미쳤다. 6. 장애자녀의 장래보장촉구에서 정신박약자 부모는 타 장애자 부모보다 통계학적으로 유의하게 불안도가 높고 저축과 유산분배도 많이 하려 하였다. 그러나 결혼에 대한 욕구는 낮으며 유산은 공공기관이나 믿을만한 타인이 맡아주기를 원하였다. 또한 생계보장보 험이나 국가로부터 지급되는 장애수당에 대해서는 양집단이 다같이 높은 관심을 보였다. 위와 같은 결과를 바탕으로 국가차원에서의 (1) 의료비제공 및 특수의료시설 지원이 있어야 하겠으며, (2) 자립작업장의 확대 및 그들의 직업훈련을 위해서 다양한 직종을 개발하고, (3) 성인수용시설 확충 및 재가장애자상담을 활성화하고, (4) 장애수당 지급, 생계 보장보험 및 유산관리를 할 수 있는 제도가 마련되어야 할 것으로 사료된다. [영문] Generally it Ms said that the birth rate of the mentally retarded is 1 or 2 percent of the total population, and that the problem of the mentally retarded is not only a family problem but also a social problem. In the meantime, the mentally retarded have net been considered a social problem in Korea and also their parents have refused to acknowledge that the children have retardation. After the International Year of disabled Persons(1981), the view point of parents to their children has changed, and their needs for their children's future security have been increasing more and more. But still people have little understanding of the mentally retarded and governmental countermeasures are not good enough yet. The objective of this study, an approach to the problems of the mentally retarded, is to determine parents' needs in the four categories of medical service, job placement, institutional care and future guarantee, and to compare them with the needs of other parents who have physically handicapped, visually handicapped, and hearing and speaking handicapped children, and finally to provide basic data to prepare better programs for the mentally retarded in the future. For this survey, a sample of 14 schools out of 94 special schools throughout the whole country was selected by cluster sampling, and a sample of 310 students also selected by systematic sampling. Finally 301 collected questionares were analysed to fond out the effective factors to the welfare needs by multiple regression analysis and also to identify the correlation among the variables by chi-square test. The results are as follows: 1. The welfare needs of parents are changed by the type and characteristics of the disabled. The longer the duration of the disability, the more difficulties the family has t? face, when the mother is older, the father's education level is higher and the disabled child is a boy, the more needs the parents have. 2. The morbidity of mentally retarded persons was lower than that of other disabled persons and the frequency of hospital utilization was the same in the two groups. But the need for medical care in the mentally retarded was higher than that of other disabled to a statistically significant level. It is considered that mentally retarded children frequently utilize a hospital not for treatment of a particular condition related to their disability but for their general health. 3. Most of all, the parents in both groups would like to see a special hospital established or a special section in a general hospital far the disabled, complaining that medical doctors in general hospitals did not have much understanding regarding the disabled and that medical fees were too high or else facilities for the disabled were not available. 4. Parents with mentally retarded children took a skeptical view of job placement and had more needs for vocational training in comparison with other parents. It can be illustrated that parents of the mentally retarded wanted sheltered workshops more than job placements in the open market. 5. The future needs for institutional care of parents with mentally retarded children were greater than that of other parents, owing to the fact that the mentally retarded cannot live alone and a family with mentally retarded family members has many difficulties in their social relations because of this. 6. Because of their anxiety over their children's future security, most of the parents were willing to leave more of their estate to their retarded children to the other siblings. But, when compared with other parents, parents with mentally retarded children did not hope to see their children marry and wanted to have their children's administrated by a public agency or other reliable persons. This was (??)tastistically significant result. And most of the parents in both groups, (?)pected to get special allowances for the disabled from the government. On the basis of the above results, the following must be considered far the welfare of the mentally retarded: new projects such as special hospitals, assistance for medical fees, special allowances and insurance far the disabled, reliable estate administration systems and extension of existing programs such as sheltered workshops, institutional care, Community Based Rehabilitation and development of a greater variety of occupation.
보건학과/석사